Urethral masson’s tumour: a rare and puzzling entity - Lim, Pei Shan; Ng, Beng Kwang; Tan, Geok Chin; Aruku N, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Intravascular papillary endothelial hyperplasia (IPEH) or Masson’s tumour is a benign vascular proliferation that mimics other malignant vascular tumour. To date, this is the fourth case of Masson’s tumour at urethra being reported in the literature. A 65-year-old female Para 2, presented with post-menopausal bleeding. Examination revealed a 4x3x3 cm growth surrounding the urethral meatus. She underwent examination under anaesthesia and excision of the periurethral mass. Histopathological examination confirmed Masson’s tumour. Diagnosis and management of this uncommon tumour at a rare location was discussed.